Advancements in understanding and addressing Alzheimer’s disease: a comprehensive review - Shakir Hussain, M.; Mishra, Ajit Kumar (International Journal of Research in Medical Sciences, 2024)
Alzheimer’s disease (AD) presents a multifaceted challenge in the realm of neurodegenerative disorders, affecting millions globally and posing significant burdens on patients, caregivers, and healthcare systems alike. Over a century of research has illuminated various facets of AD pathophysiology, highlighting the intricate interplay between genetic, molecular, and environmental factors in disease progression. This comprehensive review synthesized key findings from recent literature, encompassing diverse topics ranging from diagnostic challenges and emerging therapeutic approaches to caregiver support and evolving research strategies. Furthermore, it explored the complexities of AD pathogenesis, elucidating the role of amyloid-beta (Aβ) plaques, tau protein pathology, neuroinflammation, and mitochondrial dysfunction in neuronal degeneration. Therapeutic interventions for AD, both current and emerging, are critically evaluated, with a focus on pharmacological agents targeting Aβ aggregation, tau pathology, and synaptic dysfunction. Non-pharmacological strategies, including lifestyle modifications and cognitive interventions, are also explored for their potential in disease management. Finally, the review examined the landscape of AD research, highlighting ongoing efforts to elucidate disease mechanisms, identify novel therapeutic targets, and address existing gaps in prevention and treatment strategies. It emphasizes the need for collaborative endeavours among stakeholders to accelerate progress towards effective AD management and ultimately, improve outcomes for affected individuals and their families. Through its comprehensive synthesis of current knowledge and future directions, this review aims to inform clinicians, researchers, policymakers, and advocates involved in the fight against Alzheimer’s disease, offering insights that may catalyse advancements in diagnosis, treatment, and care.